Cumulative Subject Index on "Sample Surveys of Current Interest in India" Volume I to XIII - Planning Commission (Planning Commission, 1965)
The Central Statistical Organisation’s cumulative subject index (1948-49 to 1961-62) compiles summaries of approximately 230 sample surveys conducted across India, covering sectors such as agriculture, health, education, industry, transport, and demographics. The index categorizes surveys by central ministries and state governments, facilitating access to historical data on crop production, nutrition, disease prevalence, employment patterns, income, and socio-economic conditions. Key findings highlight disparities in health, education, and economic development between regions, as well as urban-rural differences and challenges in resource allocation. Serving as a vital resource for policymakers, researchers, and administrators, the index aids in evaluating progress, informing strategies, and planning interventions for socio-economic development and public welfare across India.
Planning Commission Statistics and Surveys Division July 1965
Planning Commission Statistics and Surveys Division July 1965
Keywords: Sample Surveys; India; Agriculture; Health; Education; Industry; Nutrition; Employment; Demographics; Socio-Economic; Rural; Urban